2015
DOI: 10.1111/mec.13404
|View full text |Cite
|
Sign up to set email alerts
|

Emerging patterns of genetic variation in the New Zealand endemic scallop Pecten novaezelandiae

Abstract: Both historical and contemporary processes influence the genetic structure of species, but the relative roles of such processes are still difficult to access. Population genetic studies of species with recent evolutionary histories such as the New Zealand endemic scallop Pecten novaezelandiae (<1 Ma) permit testing of the effects of recent processes affecting gene flow and shaping genetic structure. In addition, studies encompassing the entire distributional range of species can provide insight into colonizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 94 publications
0
10
1
Order By: Relevance
“…A low but significant level of population genetic structure has been reported for P. novaezelandiae throughout its distributional range in New Zealand (Silva and Gardner, 2015). In the present study, a weak but statistically significant isolation by distance signal was detected and different combinations of environmental variables were correlated with the genetic variation.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…A low but significant level of population genetic structure has been reported for P. novaezelandiae throughout its distributional range in New Zealand (Silva and Gardner, 2015). In the present study, a weak but statistically significant isolation by distance signal was detected and different combinations of environmental variables were correlated with the genetic variation.…”
Section: Discussioncontrasting
confidence: 47%
“…However, for P. novaezelandiae, it appears that the level of genetic differentiation is not a simple function of the geographic distance between populations. For example, it is not evident that the distance between the Chatham Islands and the mainland acts as an important barrier to larval dispersal because there is clear evidence of high levels of connectivity between these remote islands and the NZ mainland that is 850 km to the west (Silva and Gardner, 2015). Other environmental factors such as the subtropical convergence might be facilitating gene flow and thus minimizing the impact of geographic distance between the Chatham Islands and mainland New Zealand.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have suggested that this northern restriction may be related to historical processes, such as the colonization of New Zealand from the north (Silva & Gardner, 2015), along with the influence of geological processes (Stevens & Hogg, 2004). Others have suggested that coastal upwelling in the vicinity of Cape Reinga may limit the ability of species to cross this hydrodynamic feature (Veale & Lavery, 2011), or that limitations in habitat availability have restricted successful recruitment around Cape Reinga (Stevens & Hogg, 2004; Jones, Gemmill & Pilditch, 2008; Hannan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Seascape genetics as a discipline has advanced dramatically over the last decade as environmental data sets have increased in size and coverage (both spatial and temporal), and as new molecular markers and analytical tools have been developed (reviewed by [32][33][34] ). However, such work has been exclusively focused on coastal and/or shallow water) species and systems, sometimes from the perspective of environmental or evolutionary biology, and sometimes with a management (e.g., fisheries, conservation) focus (e.g., 38,[51][52][53][54][55] ). This study is amongst the first to apply the approach to deep-sea species and environments.…”
Section: Discussionmentioning
confidence: 99%